Perfil epidemiológico das infecções causadas por vírus sincicial respiratório em crianças atendidas em hospital de Fortaleza - Ce - Nunes, Ila Fernanda da Silva (2004)
Respiratory syncytial virus (RSV) is detached as an important pathogen of lower respiratory tract infections (LRTI) in children, mainly in the first year of life. This study had as purposes: to determine the prevalence of RSV in cases of acute respiratory infections (ARIs) in children served in Albert Sabin Children Hospital, in Fortaleza – CE, over the period of January 2001 to July 2004; describe the seasonality pattern of RSV circulation along the study period; observe characteristics clinical-epidemiological of these infections; characterize antigenically the circulating RSV in the epidemic period from 2003 to 2004 and determine the isolation rate of RSV in HEp-2 cells culture from samples collected in 2002, 2003, and 2004 and stored at –20ºC. Aspirated from nasopharynx were collected from children with up to seven days from the beginning of ARIs symptoms and submitted to the reaction of indirect immunofluorescence (IIF). Samples collected in 2002, 2003, and 2004, and stored at –20ºC, were inoculated in monolayers of HEp-2 cells. During the 43 months of study, RSV was identified in 21.0% (409/1950) of the clinical specimens collected. Virus circulation was initially observed during the months of January or February and the last cases were recorded in July or August of each year of study. The peak of these infections was observed from March to July, associated with the rainy season of the city. The infections caused by RSV were more frequent in male children and those with up to two years of age. Bronchiolitis and pneumonia were the clinical syndromes more associated with the virus. Dyspnea, throat pain, coryza, sneezes and cyanosis were the significant clinical signs and symptoms in ARIs caused by RSV. About 9.5 % (39/409) of the infected children presented problems associated, such as prematurity, heart diseases and congenital pulmonary diseases. Among the risk factors associated with these infections, was pointed out the exposure to ARIs in the domicile. Strains of RSV A and B co-circulated during the epidemical periods analyzed, without a significant predominance of any antigenical group. About 29.8 % (122/409) of the positive samples for RSV, stored at –20ºC, were inoculated in monolayers of HEp-2 cells. The isolation percentage varied from 0.0 %, in samples collected in 2002, to 36.8 %, in 2004. Our results confirm the importance of the RSV as etiological agent of ARIs, especially LRTI, in young children. The occurrence of RSV in the city of Fortaleza showed a regular seasonal pattern associated with the rains. The conservation of samples at –20ºC did not make impossible the isolation in cells culture up to one year after freezing.